Environmental education: the school and its contributions to the practice of conscious consumption (Research, Society and Development, 2020)
This article presents the actions of the project "Consumption and Environment" developed in the academic year of 2019 at the Rui Barbosa State School. The problem: What actions can be developed with students sensitizing them to consume with social responsibility? It aimed to develop pedagogical activities and actions aimed at sensitizing students about responsible consumption and the preservation of the Environment. The methodology was qualitative, with action research, relating theory and practice. The actions consisted of practical activities, discussions and reflections in the classroom, as well as workshops during the culmination week of the project and collection of waste for recycling. It was verified through the practices exercised by all those involved in the project “Consumption and Environment at the Rui Barbosa State School, that consuming with social responsibility and consciously disposing of waste is necessary to achieve citizenship and commitment to the environment.